Systematic Literature Review: The Effectiveness of Coaching and Mentoring in Developing Employee Performance and Leadership - Syafitri, Dinda; Umar, Haniatur Rofiqoh; Murwani, Fulgentius Danardana; Wardana, Ludi Wishnu; Ustradi Osiyo, Immanuel (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to analyze the effectiveness of coaching and mentoring in improving employee performance and leadership through a Systematic Literature Review (SLR) approach. A literature search was conducted through Google Scholar using keywords related to coaching, mentoring, performance, and leadership, resulting in 161 initial articles. After screening for publication year, scientific validity, topic relevance, and Scopus accessibility and indexing, 11 articles met the final criteria for analysis. The study results show that coaching is proven to increase motivation, work engagement, and leader self-efficacy, which directly contributes to improved performance and leadership capacity. Mentoring has been found to be effective in developing intrapersonal competencies, accelerating career development, and enhancing generative behavior for both mentors and mentees. The effectiveness of both approaches is influenced by program design, alignment with individual needs, leadership support, organizational readiness for change, and the availability of adequate learning infrastructure. Overall, coaching and mentoring are complementary human resource development strategies that only produce optimal impact when applied within a supportive organizational ecosystem.